LA ARQUITECTURA NO ES UN PRODUCTO Entrevista con el arquitecto Luca Ortelli - Valdivia Sisniegas, Richard (2010)
Actually, inside a world in globalization, the formation of future architects means an enormous responsible job. This interview is about how the formation in architecture is matter of discussion and is linked to principles. The processes to obtain academic programs make clear the involved principles that lead the life of the educational centers, in that sense, the goals of a longed for universitary accreditation could not consist only in administrative and infrastructural issues. In 0ther side, the principle of sustainability, classified just like an accomplishment of a technological environmental image for avant-garde, goes beyond th.is and can be introduced in other aspects of the carrier, that intails to take the term in an integrative way in courses of the overal formation.